Humanistic Approach in Supervision and Evaluation of Islamic Religious Education - Yanti Nurdiyanti Nurdiyanti; Zainal Arifin; Wawan Ridwan; Dodo Suhada; Mohamad Erihadiana (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Supervision and evaluation of Islamic Religious Education teachers are still experiencing obstacles so that supervision is less effective. One of them is caused by the low level of cooperativeness of teachers in the supervision process due to teachers feeling more senior and less communicative. So it needs the right approach so that the monitoring process runs effectively. This study aims to analyze the humanistic approach in the supervision and evaluation of PAI teachers at SMP Pangandaran Regency. The method used is qualitative with a case study approach. For data collection using interview and documentation techniques. Data analysis using miles and hubarman model. As well as the validity test using the credibility test with the triangulation method. The results showed that the supervision and evaluation by supervisors of PAI teachers in Pangandaran district junior high schools was carried out by: 1) Observing performance through academic supervision 2) Intensive guidance 3) Personal and group coaching 4) Development, direction to improve performance and career development 5 ) The assessment is submitted in the form of an academic supervision report. Supervision with a humanistic approach is carried out by adhering to three principles: 1) Opportunity, providing opportunities for improvement, 2) self evaluation, identifying deficiencies and exploring self-potential so as to improve teacher performance. 3) Upgrading, directing and facilitating teachers to improve competence and understand the development of information and technology.